Raudhatul Athfal Teachers’ Perceptions and Attitudes toward Hadith-Based Preventive Guidance for Early Childhood Tolerance within Islamic Guidance and Counseling - Mhd. Abror; Roby Maiva Putra; Donny Damara (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2025)
This study examines the perceptions and attitudes of Raudhatul Athfal (RA) teachers toward the use of hadith as a pedagogical and guidance-based foundation for fostering tolerance in early childhood education in the Riau Islands, Indonesia. The study responds to concerns about the emergence of intolerant behaviors among young children, including reluctance to interact with peers from different religious, ethnic, or cultural backgrounds. From the perspective of Islamic guidance and counseling, tolerance education is not merely moral instruction, but a form of preventive and developmental guidance that nurtures empathy, social acceptance, prosocial behavior, and harmonious interpersonal relationships. Hadith-based education offers an Islamic ethical framework for cultivating compassion, justice, respect for diversity, and peaceful coexistence. In RA settings, teachers serve not only as classroom educators but also as early guidance figures who support children’s internalization of Islamic values in daily social interactions. This study employed a quantitative descriptive-correlational survey design involving 250 RA teachers in the Riau Islands. Data were collected using a standardized questionnaire measuring teachers’ perceptions of hadith-based tolerance education, including knowledge, understanding, and evaluative judgment, as well as attitudes comprising cognitive, affective, and conative dimensions. Data were analyzed using descriptive statistics and Pearson’s Product-Moment correlation. The findings indicate that teachers’ perceptions were categorized as high (96%), and their attitudes were also high (98%). A strong, positive, and statistically significant correlation was found between perception and attitude (r = 0.920; p < 0.05). The study contributes to Islamic guidance and counseling by positioning hadith as a contextual resource for preventive-developmental guidance in pluralistic early childhood education.